The Community Empowerment in Improving Children's Potential and Mentality through Al-Quran Learning Center Competition at Mataram Udik Village - Diah Ratna Paramita; Riyan Erwin Hidayat; Ericca Putri Alvinata; Choirul Anwar; Danang Saputra; Riski Aji Gumelar; Umi Latifah; Nur Hidayatul Padila; Amirotun Nisfah; Adelia Permata Sari; Lailatul Mukaromah; Wiwied Pratiwi; Yeasy Agustina Sari; Haikal; Suhono, Suhono (International Journal of Community Engagement Payungi, 2024)
This article aims to increase community empowerment by exploring the potential and mentality of children can be trained in instilling religious values and train children's mentality in communicating in public through competitions Al-Quran Learning Center (TPQ). The method used ABCD (Asset Based Community Development) method. It is as a model approach in which it contains community empowerment and development. The ABCD approach is made to invite the community to recognize and explore the potential possessed by a community. The retrieval of these informants is done by interviews, observation and documentation. The data used research directly accommodated by Mataram Udik and taken from several articles from the scientific publication database Publish or Perish. Based on the results of the study, it can be concluded that there are great children who have mastered the competition materials. From these results, it can be seen that public awareness to improve human resources is still very lacking. The lack of mental training of children makes children hesitate to show their talents in public. From the competition activities, it is hoped that the people of Mataram Udik Village will start paying more attention to the importance of mental training and developing children's potential to shape children's behavior and character for the better.